Pengaruh Laba Akuntansi terhadap Return Saham : (Studi Empiris Sektor Consumer Non Cyclicals Periode 2019-2023) - Divtyajeng Nurhaliza; Sumarno Manrejo; Bambang Prayogo (Jurnal Mutiara Ilmu Akuntansi, 2025)
The aim of this research is to test and analyze the influence of accounting profit, cash flow, return on assets on stock returns. This research method uses quantitative research methods, with the type and source of data, namely secondary data. The population in this study is the non-cyclical consumer sector listed on the Indonesia Stock Exchange. The technique used is purposive sampling technique and there are 24 companies as samples with 5 years of observation. The analysis method used is a panel data regression model using eviews 12 software. The results of this study partially show that accounting profits have a positive effect on stock returns, cash flow and return on assets have no effect on stock returns.